TATA CARA UPACARA ADAT MASUK SUKU DI DESA SUNGAI PINANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Sari, Nurvita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the existence of a custom ceremony to enter the tribe in the Village Of Sungai Pinang Pujud District Rokan Hilir Regency. Where every community of immigrants who want to establish a marriage with the children of bujang or virgin In Sungai Pinang Village or the community of immigrants who want to settle in sungai pinang village must carry out custom ceremonies enter the tribe with the requirements that have been determined by Ninik Mamak, through this traditional ceremony then the immigrant community can be part of the local community or part of the tribe. The formulations of the problem in this study is how are the custom ceremony procedures to enter the tribe Sungai Pinang Village Pujud District Rokan Hilir Regency and whay the immigrant community is interested to enter the tribe in Sungai Pinang Village Pujud District Rokan Hilir Regency. The objectives of this study are to describe the procedures of traditional ceremonies entered the tribe and to find out the reason for the immigrant community interested to enter the tribe in the Sungai Pinang Village District Pujud Rokan Hilir Regency. This study uses a qualitative approach. Data collection techniques used in this study is an observation, interview, documentation and triangulation. Data analysis techniques used is data reduction, display data and verify. The findings in this research are Sungai Pinang Village people have a culture that is a custom ceremony to enter the tribe whose procedure covers. 1) Stages before the entry of the tribe is looking for adoptive parents, collection of Ninik Mamak, prepare a dish of goat curry and turmeric rice or yellow rice complete with grilled chicken, 2) phase of the ceremonial entrance that is chewing betel nut one quarter of a drop, make oral statements, submit johor set of clothes, black skull cap and sarong 2 pieces and even money 1 iya (RP. 50.000) to Ninik Mamak, the wage salaries, direction and advice and the last prayer. 3) stages after the implementation of traditional ceremonies are entering the tribe that is not allowed to enter or ride into another tribe and as for the reason the immigrant is interested to enter the tribe includes wanting to marry, gain the protection of the desire to live worthy and to be unfamiliar and the desire to gain recognition from the local community.Keywords : Adat, Enter The Tribe